Comparative Study of Methane Adsorption on Single-Walled Carbon Nanotubes - Albesa, Alberto Gustavo (2010)
We present the combined results of ab initio and molecular mechanical calculations, computer simulations, and adsorption isotherms investigations of CH₄ adsorbed on HiPco single-walled carbon nanotubes. Isotherms and adsorption energies obtained in our model and simulations are in good agreement with ours and others experimental results. The theoretical analysis conducted for various homogeneous bundles of close-ended and open-ended tubes confirm not only the adsorption in at least two different stages but also the role played by each of the different adsorption sites on the nanotube bundles. The study of different site and nanotube sizes allows us to establish the presence of open tubes in the as-produced HiPco bundles, without regarding the role that adsorption in large interstitial channels may play. Our results also show that predicted scenarios, for the mechanism and the preferential adsorption sites depend on the size of the nanotubes and those of the bundles.